OPTIMIZATION OF VALUABLE MINERALS (MG2+ & K⁺) RECOVERY FROM SEAWATER USING RESPONSE SURFACE METHODOLOGY (RSM) - Raka Selaksa Charisma Muchammad; Aisyah Alifatul Zahidah Rohmah; Caecilia Pudjiastuti; Alifah Nur Aini Fajrin; Ketut Sumada (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2025)
The extraction of metallic ions from seawater brine within a circular economy framework presents economic promise yet is hampered by concomitant ionic interference manifested during the precipitation of salts. The present investigation sought to characterize and subsequently to refine the co-precipitation steps for magnesium and potassium ions such that they yield suitable precursors for the synthesis of struvite fertilizer. The experimental work utilized a Response Surface Methodology built upon a Face-Centered Central Composite Design, interrogating the influence of the molar ratio of sodium hydrogen phosphate to calcium chloride and the duration of reaction on the simultaneous recovery of Mg²⁺ and K⁺. Results from the Analysis of Variance demonstrated that the principal effects of the aforementioned ratio, reaction duration, and their interaction terms were statistically significant for both target recoveries. By iterative optimization, the experimental framework predicted optimal operational parameters of sodium hydrogen phosphate to calcium chloride ratio of 0.401 and a reaction interval of 11.608 minutes, corresponding to a composite desirability statistic of 0.908 and estimated recoveries of 93.979 % and 97.300 % for magnesium and potassium ions, respectively. The data therefore substantiate the conclusion that Response Surface Methodology provides a systematic and analytically tractable conduit for the resolution of equilibrated brine mixtures, delineating a refined process envelope that promotes the extraction and economic valorization of essential mineral fertilizers from industrial saline streams.